Estimating saving and investment functions in Pakistan - Afzal, Mohammad (2004)
This paper estimates simultaneously the saving and investment functions for Pakistan for the period 1960-2003. Compared with other Asian countries, Pakistan has not experienced adequate growth in national savings. Growth of real GDP, real per capita income, foreign capital inflow and investment are found to be the major determinants of savings. The findings support the 'displacement hypothesis'. On the other hand, macroeconomic stability, inflation, availability of domestic credit, exchange rate, and foreign and national saving have been found to be the most crucial factors influencing the investment environment. Macroeconomic stability and the pursuit of sound macroeconomic policies can augment both saving and investment.
Title was 'Philippine Review of Business and Economics' until 1979. Title changed to 'Philippine Review of Economics and Business' from 1980-2000, and again changed to 'Philippine Review of Economics' since 2001.
Includes bibliographical references (pages 77-78)
Keywords: Saving and investment -- Pakistan; Monetary policy -- Pakistan; Pakista -- Economic policy